"The persistent myth of lost hegemony, " revisited: structural power as a complex network phenomenon. (September 2020) - Winecoff, William Kindred
This article resuscitates the idea of structural power in world politics by linking it to modern complex network science, presents a theoretical framework for understanding how global structures develop and change, and empirically analyzes the prominence of leading states within global finance, trade, security, and knowledge networks. It argues that the "fitness plus preferential attachment" (FPA) model of complex network evolution provides a logical explanation for the durability of American influence even as some of its advantages in country-level capabilities has eroded, and it introduces a network methodology that is capable of empirically analyzing the organizational complexity that exists within and across domains in world politics. It argues that the rise of China and other emerging powers has been overstated in some ways, but that a redistribution of structural prominence is taking place, in some domains, as emerging markets increase their transnational connections; this has mostly come at the relative expense of Europe, however, rather than the United States.